Recent Advances in Functionalized Nanoporous Carbons Derived from Waste Resources and Their Applications in Energy and Environment. (3rd September 2020) - Joseph, Stalin; Saianand, Gopalan; Benzigar, Mercy R.; Ramadass, Kavitha; Singh, Gurwinder; Gopalan, Anantha‐Iyengar; Yang, Jae Hun; Mori, Toshiyuki; Al‐Muhtaseb, Ala'a H.; Yi, Jiabao; Vinu, Ajayan
Abstract: Nanoporous carbon materials have been widely utilized for myriad applications owing to their intriguing physicochemical properties. Development of green and clean synthetic techniques/procedures to generate nanoporous carbon materials especially derived from inexpensive waste precursors/resources has rejuvenated the chemistry of carbon materials owing to the abundant nature and low cost of these sources and their ability to generate unique surface/porous structures. These nanoporous carbon materials have been heavily explored in multiple sectors such as soil/water remediation, adsorption and separation, catalysis, energy storage/conversion, capture and conversion of carbon dioxide. In this topical review, the recent state‐of‐the‐art research progress achieved in the design and development of waste‐derived advanced functionalized porous carbon materials are summarized. The various lab‐specific approaches and methodologies involved in synthesizing these materials are discussed in detail. In addition, the potential applications of waste‐derived functionalized porous carbons in the fields of environment, energy storage, and conversion applications are highlighted. Finally, a discussion on a few suggestions for future research is concluded. It is believed that this review provide inspiration for many new research activities over a wide range of disciplines. Abstract : Development of green synthetic procedures to generate nanoporous carbon materials derived from inexpensive waste resources has rejuvenated the chemistry of carbon materials. In this topical review, the recent state‐of‐the‐art research progress achieved in the design and development of waste‐derived advanced functionalized porous carbon materials along with their potential application in the fields of environment, energy storage and adsorption are summarized.